Designing an E-Booklet Script to Promote Semendo Coffee from South Sumatera - Syahputri, Larasati (Politeknik Negeri Sriwijaya, 2023)
ABSTRACT: This study aimed to develop a booklet to promote Semendo Coffee from South Sumatera. This research methodology was Research and Development (R&D) modified by Plom, T. (1997). The stages were 1) Preliminary investigation, 2) Design, 3) Realization/Construction, 4) Test, Evaluation, and 5) Revision, and Implementation. To achieve the purpose, the stages of research and Development were linked to the structure by Sitepu (2004) namely the cover, front part, text part, and back part. Then an ebooklet was made from the promotional media. This e-booklet was tested by an expert. The script was written in English and the design used Canva as the software. The script described the history of Semendo Coffee at PT. Cap Sendok Mas, Process of Semendo Coffee, and Marketing at PT. Cap Sendok Mas. Keywords: design, e-booklet, Semendo Coffee from South Sumatera